2017
DOI: 10.3892/ijmm.2017.3208
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents osteoporosis by upregulating FoxO1 transcriptional activity

Abstract: Resveratrol (3,5,4-trihydroxystilbene, RES), a natural antioxidant, prevents bone loss by attenuating damage caused by oxidative stress. Our previous research revealed that the forkhead box O1 (FoxO1)/β-catenin signaling pathway affected the proliferation and differentiation of osteoblasts through its regulation of redox balance, and RES regulated the expression of FoxO1 to control white adipose tissue and then ameliorate an overweight condition. Based on previous research, we hypothesized that RES regulates F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 56 publications
2
62
1
5
Order By: Relevance
“…It has been reported that resveratrol promoted wound healing in diabetic 47 or increased glycolysis 48 by inhibiting FoxO1. However, the opposite results have also been reported which showed that resveratrol upregulated FoxO1 transcriptional activity in preventing osteoporosis 49 or regulating oxidative stress and apoptosis of renal. 50 In the present study, we found that either resveratrol or IL-1β treatment could activate PI3K/Akt signaling and inactivate FoxO1 in a time-dependent manner in SW1353 cells.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that resveratrol promoted wound healing in diabetic 47 or increased glycolysis 48 by inhibiting FoxO1. However, the opposite results have also been reported which showed that resveratrol upregulated FoxO1 transcriptional activity in preventing osteoporosis 49 or regulating oxidative stress and apoptosis of renal. 50 In the present study, we found that either resveratrol or IL-1β treatment could activate PI3K/Akt signaling and inactivate FoxO1 in a time-dependent manner in SW1353 cells.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have indicated the beneficial effects of sirtuins as the best small molecule that activate sirtuins, which extended lifespan in a yeast model [104][105][106][107][108][109]. Although only the longevity extension effect of resveratrol has been reported in C. elegans and D. melanogaster, many subsequent studies reported that resveratrol intake promotes health and plays a preventive role in age-related diseases, such as cancer [110][111][112][113], atherosclerosis [114,115], arthritis [116,117], cataract [118][119][120], cardiovascular disease [121], hypertension [122,123], type 2 diabetes [124][125][126][127], osteoporosis [128][129][130], and Alzheimer disease [131][132][133]. In clinical studies, resveratrol intake improved the memory capacity of elderly individuals and reduced blood lipid levels in obese and type 2 diabetic patients [134,135].…”
Section: Resveratrolmentioning
confidence: 99%
“… 9 12 RES could effectively prevent bone loss, as indicated by the in vitro experiments in rats, which lost bone mass due to lack of physical activity and estrogen deficiency. 13 RES inhibits the synthesis of reactive oxygen species, resulting in an increase in the alkaline phosphatase levels and proline hydroxylase activity in MC3 T3-E1 cells and prevention of the differentiation of RAW264.7 cells into osteoclasts. 14 , 15 However, the mechanism of action of RES remains unclear and needs further analysis.…”
Section: Introductionmentioning
confidence: 99%